Rekonstruksi Rezim Hukum Laut Internasional terhadap Aktivitas Grey Zone Maritim dalam Kerangka Unclos 1982 - Arintika Noriyah (Jurnal Hukum Lex Generalis, 2026)
Maritime security dynamics have shifted toward ambiguous grey zone activities that are difficult to address under international law. This study examines the normative limitations of UNCLOS 1982 and proposes its reconstruction using a normative juridical method with statutory and conceptual approaches. The findings reveal legal lacunae in the definition of actors, the regime of sovereign immunity and the right of visit. This article not only describes grey zone activities but also offers novelty through normative reconstruction via evolutive interpretation, strengthening regional frameworks as lex specialis and reformulating state attribution to enhance legal certainty and protect coastal state sovereignty.